"Anything Worthwhile Takes Time": Eight Schools Discuss Impacts and Impressions of Doing Action Research - Janet Benton; Jean Wasco (Networks: An Online Journal for Teacher Research, 2000)
During the 1997-1998 school year, eight elementary, middle, and high schools connected with each other and a local university to conduct classroom-based action research, and our goal in these reflections is to examine what the teachers involved in the studies thought about the research process and the possible effects of action research on their students' classroom performances.